Bank production with nonperforming loans: A minimum distance directional slack inefficiency approach. (December 2022) - Fukuyama, Hirofumi; Matousek, Roman; Tzeremes, Nickolaos G.
Abstract: The study examines a bank production process with nonperforming loans in Japanese banking. Banks' production process is measured by utilizing a minimum distance directional slack inefficiency model and by treating nonperforming loans through using the costly disposability property. Japanese banks' performance levels are evaluated over the period 2013–2019. The estimated banks' minimum distance directional slack inefficiency measure is further decomposed into labor, physical capital, loan, investment and strategic (decision) inefficiency. Empirical findings indicate substantial inefficiencies in Japanese banking that are mainly attributed to the hard-to-achieve targets set by the standard directional slack inefficiency model which is based on Koopmans' notion of strong efficiency. The proposed minimum distance directional slack inefficiency estimator provides bank managers with practical targets, by evaluating banks at the closest point on the strongly efficient frontier. Finally, the empirical evidence suggests that the key factors behind Japanese banks' performance are high investment and strategic (decision) efficiency levels.